Optimal Convergence Analysis of a Mixed Finite Element Method for Fourth-Order Elliptic Problems (Communications in Computational Physics, 2018)
A Ciarlet-Raviart type mixed finite element approximation is constructedand analyzed for a class of fourth-order elliptic problems arising from solving variousgradient systems. Optimal error estimates are obtained, using a super-closeness relation between the finite element solution and the Ritz projection of the PDE solution.Numerical results agree with the theoretical analysis.